HEMICHOREA: AN UNUSUAL MANIFESTATION OF THYROTOXICOSIS - Rao S, Raghavendra; Seshadri, Shubha; Rao N, Karthik; Patil, Navin; Kunder, Sushil Kiran; Avinash, A (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Chorea is usually associated with neurological diseases. However, it can also be seen in patients with systemic lupus erythematosus (SLE), rheumatic fever (Sydenham's chorea), polycythemia vera, and thyrotoxicosis. Here, we report an interesting case of hemichorea in a 32-year-old lady, who presented with acute onset of jerky, non-repetitive involuntary movements of the left upper and lower limbs. After detailed evaluation, she was found to have thyrotoxicosis. Thyroid Tc-scan showed diffuse uptake suggesting Grave's disease. A magnetic resonance imaging of the brain was normal. Other causes of chorea like SLE and rheumatic fever were excluded. She was started on carbimazole. On follow-up after 6 weeks of therapy, there was the complete disappearance of chorea, and her thyroid hormone levels were normal. Keywords: Extrapyramidal syndrome, Hyperthyroidism, Corpus striatum, Dancing movements.